The ornament of histories - Gardīzī, ʻAbd al-Hayy ibn Zahhāk. (London ; New York)
xiii, 169 sayfa
Keywords: “Abu Sa’id ‘Abd al-Hayy Gardizi was an author and historian living in the mid-eleventh century at the height of the Turkish Ghazvanid dynasty. His only known work, The Ornament of Histories (‘Zayn al-akhbir’), is a hugely ambitious history of the Eastern Islamic lands AD 650-1041, spanning what is now Eastern Iran, Afghanistan and parts of the Central Asian Republics and Indo-Pakistan subcontinent. Gardizi’s text is an extremely rare source of primary information about the rise of Islamic faith, culture and military dominance in these regions, and represents a significant contribution to our understanding of the early Islamic world. This is the first English translation of the original Persian text, and is accompanied by an introduction and commentary which details the historical, geographical and cultural context.” --